Enzyme-instructed self-assembly of taxol promotes axonal branching. Issue 38 (11th September 2015) - Mei, Bin; Miao, Qingqing; Tang, Anming; Liang, Gaolin
Abstract : ALP-instructed self-assembly of taxol promotes axonal branching. Abstract : Axonal branching is important for vertebrate neuron signaling. Taxol has a biphasic effect on axonal branching ( i.e., high concentration inhibits axonal growth but low concentration restores it). To the best of our knowledge, low concentration of taxol to promote axonal branching has not been reported yet. Herein, we rationally designed a taxol derivative Fmoc-Phe-Phe-Lys(taxol)-Tyr(H2 PO4 )-OH (1 ) which could be subjected to alkaline phosphatase (ALP)-catalyzed self-assembly to form taxol nanofibers. We found that, at 10 μM, 1 has a microtubule (MT) condensation effect similar to that of taxol on mammalian cells but with more chronic toxicity than taxol on the cells. At a low concentration of 10 nM, 1 not only promoted neurite elongation as taxol did but also promoted axonal branching which was not achieved by using taxol. We propose that self-assembly of1 along the MTs prohibited their lateral contacts and thus promoted axonal branching. Our strategy of enzyme-instructed self-assembly (EISA) of a taxol derivative provides a new tool for scientists to study the morphology of neurons, as well as their behaviours.